Musa beat: en viaje hacia la redención - Dardo Scavino (Cuadernos LIRICO)
In this article, we try to demonstrate that a series of songs published in 1969 are the basis of what we call the code, or the muse, beat, a mythology that journalists would call from the following year «rock national». This mythology has survived until today. It consists, in our opinion, on two classic genres, the exhortation and exemplum, away from two neighbouring musical expressions: political protest song and romantic love song.